Efficacy and safety of isavuconazole against deep-seated mycoses: A phase 3, randomized, open-label study in Japan. Issue 2 (February 2023) - Kohno, Shigeru; Izumikawa, Koichi; Takazono, Takahiro; Miyazaki, Taiga; Yoshida, Minoru; Kamei, Katsuhiko; Ogawa, Kenji; Taniguchi, Shuichi; Akashi, Koichi; Tateda, Kazuhiro; Mukae, Hiroshi; Miyazaki, Yoshitsugu; et al.
Abstract: Objectives: Isavuconazole is a convenient triazole antifungal agent with a broad antifungal spectrum. A randomized, open-label study (ClinicalTrials.gov, NCT03471988) was conducted to evaluate the efficacy and safety of isavuconazole in Japanese patients with deep-seated mycoses. Patients and methods: In Cohort A, patients with aspergillosis (chronic pulmonary aspergillosis and invasive aspergillosis) were randomized in a 2:1 ratio to isavuconazole or voriconazole, and in Cohort B, patients with cryptococcosis and mucormycosis were assigned to isavuconazole for up to 84 days of treatment. The overall outcome was evaluated according to the clinical, radiological, and mycological responses at Days 42 and 84 and at the end of treatment (EOT). Results: A total of 103 participants were enrolled and received the study drug. The overall response rate of patients with chronic pulmonary aspergillosis in the isavuconazole (52 patients) and voriconazole (27 patients) groups was 82.7% and 77.8% at EOT, respectively. The response rate in patients with cryptococcosis (10 patients, isavuconazole group only) was 90.0%. One of three participants with invasive aspergillosis and one of three participants with mucormycosis responded in the isavuconazole group. In the safety evaluation, the incidence of adverse events in participants with chronic pulmonary aspergillosis was similar in both groups. Adverse drug reactions were reported in 32 (61.5%) patients receiving isavuconazole and 23 (85.2%) patients receiving voriconazole. Conclusions: Isavuconazole showed efficacy and safety in Japanese patients with chronic pulmonary aspergillosis and cryptococcosis, for which the drug is not currently indicated.